Tantangan Implementasi Program B40 di Indonesia: Tinjauan Teknis dan Ketersediaan Bahan Baku Biodiesel - Eka Alel, Ariya; Hastuti, Ririn Puji; Legawati, Lisa (SURYA TEKNIKA, 2025)
The B40 program is a continuation of Indonesia’s mandatory biodiesel policy, which requires blending 40% palm oil–based biodiesel with 60% conventional diesel fuel. This program aims to reduce dependence on fossil fuel imports while supporting national greenhouse gas emission reduction targets. This study analyzes the challenges of B40 implementation in Indonesia, focusing on feedstock availability as well as technical aspects of biodiesel production and distribution. The research employs a desk study approach using secondary data from GAPKI, BPDPKS, the Ministry of Energy and Mineral Resources, and relevant scientific literature. The results indicate that Indonesia’s crude palm oil (CPO) production in the first half of 2025 reached approximately 27.89 million tons, while the CPO requirement for B40 is projected at around 13.5 million tons. The installed capacity of the national biodiesel industry is about 20 million kiloliters per year, exceeding the projected B40 biodiesel demand of 15.6 million kiloliters. However, technical challenges remain, including biodiesel quality issues, dependence on imported methanol, and distribution constraints in remote regions. Overall, the B40 program has the potential to reduce emissions by approximately 25–28 million tons of CO₂-equivalent per year and contribute to Indonesia’s energy transition.